Health care and patients' education in a European inflammatory bowel disease inception cohort: An ECCO-EpiCom study. (1st August 2014) - Burisch, J.; Vegh, Z.; Pedersen, N.; Čuković-Čavka, S.; Turk, N.; Kaimakliotis, I.; Duricova, D.; Bortlik, M.; Shonová, O.; Thorsgaard, N.; Krabbe, S.; Andersen, V.; et al.
Abstract: Background and Aims: The EpiCom study and inception cohort was initiated in 2010 in 31 centers from 14 Western and 8 Eastern European countries, covering a 10.1 million person background population. Our aim was to investigate whether there is a difference between Eastern and Western Europe in health care and education of patients with inflammatory bowel disease (IBD). Methods: A quality of care (QoC) questionnaire was developed in the EpiCom group consisting of 16 questions covering 5 items: time interval between the onset of symptoms and diagnosis, information, education, empathy and access to health care providers. Results: Of 1, 515 patients, 947 (217 east/730 west) answered the QoC questionnaire. Only 23% of all patients had knowledge about IBD before diagnosis. In Eastern Europe, significantly more patients searched out information about IBD themselves (77% vs. 68%, p < 0.05), the main source was the Internet (92% vs. 88% p = 0.23). In Western Europe, significantly more patients were educated by nurses (19% vs. 1%, p < 0.05), while in Eastern Europe, gastroenterologists were easier to contact (80% vs. 68%, p < 0.05). Conclusion: Health care differed significantly between Eastern and Western Europe in all items, but satisfaction rates were high in both geographic regions. Because of the low awareness and the rising incidence of IBD, general information should be the focus of patient organizations and medical societies. In Western Europe IBD nurses play a very important role in reducing the burden of patient management.